Assessing prevalence and predictors of depression in Type 2 Diabetes Mellitus (DM) patients – The DEPDIAB study. (August 2021) - Majumdar, Sujoy; Sinha, Binayak; Dastidar, Biswajit Ghosh; Gangopadhyay, Kalyan Kumar; Ghoshal, Samit; Mukherjee, Jagat Jyoti; Mazumdar, Anirban; Ray, Subir; Dasgupta, Samir; Bhattacharjee, Kingshuk
Abstract: Objectives: Depression is common in diabetes and has significant impact on health outcomes. Suicidal ideation also forms a part of the spectrum of diabetes and coexistent depression. To assess the predictors of depression as well as its prevalence in Type 2 Diabetes Mellitus (T2DM) patients, we conducted a cross sectional study entitled "DEPression in DIABetes" (DEPDIAB). Material and methods: A cohort of consecutive 1371 T2DM patients from Eastern India suffering from diabetes greater than 1 year was assessed in a cross- sectional survey in 9 different hospitals and medical polyclinics in Kolkata, India for depression by administering the 9-item PHQ – 9 and Beck depression scales. Socioeconomic status was assessed by the "Revised Kuppuswamy and B G Prasad socio-economic scales for 2016", a validated scoring system for assessing the socioeconomic status of Indian patients. Results: In our study 836 patients (60.9%) were male and 535 (39.02%) were female. 56 patients (4.1%) met the criteria for major depression and 494 patients (36.16%) for minor depression. No sign of depression was found in 816 patients (59.74%). Depression was strongly associated with younger age (18–40 years vs. >60 years) [OR-2.09; 95% CI 1.11–3.96], female sex [OR-1.31; 95% CI 1.11–2.01], low socioeconomic status [OR-2.69; 95% CI 1.34–3.79], poor compliance [OR- 5.05; 95% CI 2.79–8.13], hypoglycemia [OR 1.466; 95% CI 1.076–1.999] and difficulty in managing day-to-day activities [OR- 4.648; 95% CI 3.450–6.262] Suicidal ideation was detected in 201 patients (14.8%). Among patients who had repeated attacks of hypoglycemia (>1 episode per month), 22% experienced suicidal ideation. This was significantly higher than in patients who had not suffered from hypoglycemia (12%) (p < 0.0001). Patients with HbA1C of 7% or lower experienced statistically significantly lesser suicidal ideation than patients with a higher HbA1C (12% vs. 16.8% p = 0.016). Suicidal ideation did not correlate withbody mass index (BMI), fasting plasma glucose (FPG) or insulin usage. Conclusions: We found a high prevalence of depression in T2DM patients in Eastern India. Younger age, female sex, lower socio-economic status, poor compliance, hypoglycemia, and difficulty in managing day to day activities emerged as significant predictors of depression in this study. Recurrent episodes of hypoglycemia were an independent risk factor for suicidal ideation in patients with depression. Depression was not significantly associated with co morbidities associated with T2D and surprisingly insulin usage was not associated with increased depression.